2021
DOI: 10.4108/eai.29-6-2021.170250
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the least air polluted path using the neural network approach

Abstract: Air pollution exposure during daily transportation is becoming a critical issue worldwide due to its adverse effect on human health. Predicting the least air polluted healthier path is the best alternative way to mitigate personal air pollution exposure risk. Computing the least polluted path for the current time might not be helpful for real-time applications. Therefore, we develop a routing algorithm based on a neural network-based CNN-LSTM-EBK (CLE), a temporal-spatial interpolation model. The proposed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…However, the impact can be mitigated if the individual's environment can be more positive. Some environmental factors that may trigger or lead to antisocial behavior are exposure to community violence, family dysfunction, and peer influence [8,27,28].…”
Section: Etiology Of Antisocial Behaviormentioning
confidence: 99%
“…However, the impact can be mitigated if the individual's environment can be more positive. Some environmental factors that may trigger or lead to antisocial behavior are exposure to community violence, family dysfunction, and peer influence [8,27,28].…”
Section: Etiology Of Antisocial Behaviormentioning
confidence: 99%
“…This was accomplished by implementing the Empirical Bayesian Kriging (EBK) model during the geospatial analysis phase. In a subsequent work [17], the authors extended their approach by incorporating convolutional neural networks to extract features and utilising long short-term memory models for capturing the sequential dependency of air quality. The results consistently demonstrated that although the predicted path might be longer than the shortest route, it effectively minimises the risk of pollution exposure.…”
Section: Related Workmentioning
confidence: 99%